A history of German Jewish Bible translation - Gillman, Abigail (The University of Chicago Press, 2018)
Intro -- Contents -- Preface -- List of Abbreviations -- Introduction: The German Jewish Bible in Context -- 1. The First Wave: Jewish Enlightenment Bibles in Yiddish and German -- 2. The Second Wave: Emergence of a Bible Industry -- 3. The Third Wave: The Bible as Gesamtkunstwerk -- 4. The Fourth Wave: Reimagining the German Jewish Bible -- Epilogue: Ma shemo? The Name of God in the German Jewish Bible -- Acknowledgments -- Notes -- Bibliography -- Index